Relevance of Positive Dyadic Coping for Couples Undergoing Assisted Reproduction Treatments: A Systematic Review. - Santamaría‐Gutiez, Rebeca; Martínez‐Corredor, Silvia; González‐Sala, Francisco; Lacomba‐Trejo, Laura (Journal of Marital & Family Therapy, 2025)
The present study investigates the impact of positive dyadic coping strategies on the physical and mental health of couples undergoing assisted reproductive treatments (ART). A systematic literature search was conducted in databases, including ProQuest, PubMed, Scopus, and Web of Science, adhering to the PRISMA guidelines. From an initial pool of 1061 studies, 23 were selected for final analysis, encompassing a total of 7079 participants. The findings indicate that positive dyadic coping may significantly enhance mental health, couple adjustment and satisfaction, self‐esteem, and quality of life in couples undergoing ART. The quality of the included studies was rated as moderate to high. The study concludes that integrating positive dyadic coping strategies into psychological intervention programs and providing psychological support within the healthcare system may be essential for couples undergoing ART.